2022
DOI: 10.3390/ijerph19073916
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Accessing Eye Health Services in Suburban Communities in Nampula, Mozambique

Abstract: Globally, an estimated 2.2 billion people are visually impaired (VI) or blind, and a large proportion (90%) of those affected live in low- and middle-income countries (LMICs), where access to eye health services is limited. This study aimed to identify barriers to accessing eye health services and associated factors in suburban communities of Nampula. A cross-sectional community-based study was carried out on adults ≥18 years old. A total of 338 adults were randomly selected from three communities (Muthita, Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…This results in overcrowding in public hospitals, longer waiting time in health facilities or in long distances to travel to enjoy eye health services, with additional transport costs. These factors constitute barriers to access to eye health services and a major obstacle in the fight against preventable and treatable VI [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This results in overcrowding in public hospitals, longer waiting time in health facilities or in long distances to travel to enjoy eye health services, with additional transport costs. These factors constitute barriers to access to eye health services and a major obstacle in the fight against preventable and treatable VI [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Refractive errors stand out among the main causes of visual impairment after cataract surgery. Studies performed in Mozambique have shown that the acquisition of corrective glasses is still not easily accessible for a large proportion of the population of Nampula, with financial difficulties being indicated as the main barrier, in a country where 49.9% of the population lives in conditions of severe poverty [ 27 , 28 ], resulting in the circumstance that some people who undergo surgery can continue having visual deficiencies due to uncorrected refractive errors. Therefore, for our study, the presenting visual acuity (with the available correction) was used as a reference over visual acuity with better correction since it better reflects the daily reality of the patient, being more associated to the characteristics that wish to be measured such as VFm and QoLm.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show that some patients undergo cataract surgery when aspects of their VF and QoL are already very debilitated, compromising the psychosocial well-being of the individual and his family. Therefore, these instruments (VFm and QoLm) may also help in the management and decision making by clinicians, such as, for example, the choice of the best time to operate, since studies have revealed that one of the barriers of access to cataract surgery has been the fact that “the cataract is not yet mature enough” [ 28 , 30 – 32 ] leading the doctor or the patient to choose to wait for the appropriate time to perform the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sengo et al performed a literature review and interviewed 25 people in Mozambique with vision impairment to identify which barriers should be used in a wider survey. 34 However, the exercise was inadequately described and the authors do not provide any detail on how the qualitative data were analysed.…”
Section: Introductionmentioning
confidence: 99%